(sinQ +1 +CosQ ) (sinQ -1 +CosQ). secQ cosecQ =2
Answers
Answered by
2
Step-by-step explanation:
(sinQ+cosQ+1) (sinQ+cosQ-1)secQcosecQ
={(sinQ+cosQ)²-1²} secQcosecQ
={1+2sinQcosQ-1) secQcosecQ
=2sinQcosQsecQcosecQ
=2
Answered by
3
Answer:
Step-by-step explanation:
To prove ,
(sinQ + 1 + cosQ ) (sinQ - 1 + cosQ) secQ cosecQ = 2
LHS
( sinQ + cosQ + 1 ) ( sin Q + cos Q + 1 ) secQ cosecQ .
{(sinQ + cosQ )² - 1²} secQ cosecQ
{sinQ² + cosQ² + 2 sinQ cosQ - 1} secQ cosecQ
{1 - 1 + 2 sinQ cosQ} = 2
∴ LHS = RHS
Similar questions